The Sources of War Finance in The German War Economy - Singer, H. W. (Review of Economic Studies, 1943)
The Sources of War Finance in The German War Economy Get access H. W. Singer H. W. Singer Manchester Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 10, Issue 2, Summer 1943, Pages 106–114, https://doi.org/10.2307/2967427 Published: 01 July 1943